PA clinical postgraduate training: A half-century of development. Issue 5 (May 2022) - Grabenkort, Rob; Hilton, Ginny
ABSTRACT: Clinical postgraduate training (CPGT) for physician assistants (PAs) began in 1971. A half-century later, the United States has 144 programs in 33 specialties. A growing and aging population, specialization in healthcare, and changes in graduate medical education have created new opportunities for PAs to consider this alternative following graduation. Postgraduate training is attractive to PA graduates who desire advanced skills and deeper understanding in a medical or surgical specialty. This article describes the history of CPGT programs, training, and establishment of an accreditation process for educational standardization.